The longitudinal association between possible new sarcopenia and the depression trajectory of individuals and their intimate partners - Tian, Yufeng; Hu, Zhigang; Song, Xinyu; Yang, Ailan (Frontiers in Aging Neuroscience, 2022)
Background: Whether the dynamic nature of depression affects the development of sarcopenia is currently unknown. Herein, this study plans to assess the association between newly possible sarcopenia with depression trajectory of individuals and their intimate partners through a four-year longitudinal cohort study. Methods: Our study included 784 pairs of individuals without possible sarcopenia and their spouses from the China Health and Retirement Longitudinal Study 2011. All individuals and their spouses received three assessments of the Center for Epidemiologic Studies Depression 10-item (CESD-10) scale in 2011, 2013 and 2015. According to the recommended diagnostic algorithm of the Asia Working Group for Sarcopenia 2019, we evaluated the incidence of possible sarcopenia of individuals in 2015. Latent class analysis was used to identify longitudinal trajectory of depression of individuals and their spouses during 4-year follow-up. Subsequently, we assessed the relationship between possible sarcopenia and depression trajectory by three generalized additive models. Results: In 2015, 24.87% (195/784) of individuals were diagnosed with possible sarcopenia. Latent class analysis identified five depression trajectories: persistently high risk of depression in individuals and their spouses (reference; Class 1 =34 [4.3%]); persistently low risk of depression in individuals and their spouses (Class 2=526 [67.1%]); high risk of depression in individuals and low risk of depression in spouses (Class 3=46 [5.9%]); low risk of depression in individuals and high risk of depression in spouses (Class 4=116 [14.8%]); decreasing risk of depression in individuals and their spouses (Class 5=62[7.9%]). The highest incidence of possible sarcopenia was shown in class 1, followed by class 3 and class 5. Class 2 (adjusted RR=0.44, 95%CI:0.20-0.97) and class 4 (adjusted RR=0.40, 95%CI:0.17-0.96) were associated with significantly lower incidence of possible sarcopenia than class 1. Subgroup analysis demonstrated that the incidence of possible sarcopenia in class 4 was obviously higher in female (38.89%) than that in male (18.4%). Conclusions: Our study indicates that persistently high risk of depression in individuals has the higher risk of developing possible sarcopenia. In addition, persistently high risk of intimate partners’s depression potentially increases the risk of newly possible sarcopenia, especially in female individuals with low-risk depression.